The Impact of Artificial Intelligence and Automation on Employment in Indonesia’s Manufacturing Sector: A Sociological Analysis - Ngr. Putu Raka Novandra Asta; Azamat Nazarov; Joao Silva (Yayasan Adra Karima Hubbi, 2025)
Background. The rapid advancement of Artificial Intelligence (AI) and automation has revolutionized various industries globally, including Indonesia’s manufacturing sector. The integration of these technologies has raised concerns about their impact on employment, particularly regarding job displacement and skill requirements. While AI and automation offer opportunities for increased productivity and efficiency, they also pose challenges for workers, especially in a developing economy like Indonesia. Purpose. This study aims to explore the sociological impact of AI and automation on employment in Indonesia’s manufacturing sector, focusing on the potential changes in the labor market, skill gaps, and social implications for workers. Method. The research employs a mixed-methods approach, combining both qualitative and quantitative techniques. Surveys were conducted with workers in the manufacturing industry, and in-depth interviews with industry experts and sociologists were also carried out. Data was analyzed using thematic coding for qualitative data and statistical analysis for quantitative data to examine the relationship between technological advancements and employment trends. Results. The findings indicate that AI and automation are contributing to job displacement, especially for low-skilled workers, while creating new opportunities for highly skilled labor in areas such as robotics maintenance and data analysis. However, there is a significant gap in workers’ ability to adapt to new technologies due to insufficient training and education. Conclusion. The study concludes that there is a need for strategic policies focused on reskilling and upskilling the workforce to mitigate the adverse effects of automation on employment.